Purwarupa Pendeteksi Karbon Monoksida dalam Ruang Kendaraan Roda Empat Berpendingin AC ( Air Conditioner ) Berbasis DFRduino Uno R3 - , KHOIRI NURRAHMANI, Ariesta Martiningtyas H., S.Si ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Carbon Monoxide is categorized as one of the harmful gas for human. Carbon Monoxide is a gas that cant be smell, have no colour, and cant be tasted. This gas can be emitted by leakage of car Air Conditioner. The purpose from this research is to design a system as the prevention step from the carbon monoxide harmful effect in the car cabin. This system consist of software and hardware. The software using C language in DFR Duino. The hardware using 5 volt and 12 volt power supply. The CO gas sensor using TGS 2442, microcontroller using DFR Duino, LCD as the display for the information, buzzer as the sound output, and schematic of H-Bridge as the rotor of DC motor. The working principle from this system is whether the amount of C O in cabin car reaching 100 ppm and then the car window will be open and also activating the buzzer as the warning indicator. The result of the experiment known that the working principle of the CO gas detector can work well and the average value shown increased significant graph from the clean air until contaminated CO air.